2016
DOI: 10.1016/j.jadohealth.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Correlates of Preventive Behaviors at First Sex With a First Partner and Second Partner: Analysis of the FECOND Study

Abstract: Purpose This study explores transitions in contraceptive use in early sexual life in France and has three objectives: describe predictors of contraceptive use at first sex with first and second partners, describe contraceptive trajectories in these partnerships, and test associations between use at first sex and switching in first partnership on use with second partner. Methods Our analyses include 1,823 participants, aged 15-29, of the 2010 French national sexual health survey who reported at least 2 lifeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
1
4
0
1
Order By: Relevance
“…We also found that as the number of sexual partners increased, the odds of pill discontinuation increased. This result may relate to our prior discussion about the need for STI prevention with new partners, which may lead some women to switch from pills to condoms when they start a new relationship [34]. In contrast, condom users at the start of their sexual lives (less than 1 year of sexual experience) were more likely to discontinue, a finding that corroborates the results of a previous study in Honduras [38].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We also found that as the number of sexual partners increased, the odds of pill discontinuation increased. This result may relate to our prior discussion about the need for STI prevention with new partners, which may lead some women to switch from pills to condoms when they start a new relationship [34]. In contrast, condom users at the start of their sexual lives (less than 1 year of sexual experience) were more likely to discontinue, a finding that corroborates the results of a previous study in Honduras [38].…”
Section: Discussionsupporting
confidence: 83%
“…Other studies have pointed to the strong connection between partnership and contraceptive use dynamics. Among couples, condoms are mainly used during casual relationships or in the beginning of a relationship to prevent against Sexually Transmitted Infections (STIs) and are replaced by more effective contraception in more stable relationships [25, 34]. As relationships become more stable, many couples switch to hormonal methods, and the main reason to switch is the “supposed mutual trust”.…”
Section: Discussionmentioning
confidence: 99%
“…Young men generally attribute this behavior change to low or no concern for STIs. The use of condoms in long-term relationships can even take on a negative connotation, as a sign of infidelity [7,9]; with a quarter of United States and French men discontinuing condom use before the end of their first relationship [10,11▪]. This transition period from a casual to a long-term relationship may be a time of high pregnancy risk, with a gap between cessation of condom use and initiation of female hormonal contraception [7].…”
Section: Young Men’s Views On Contraceptionmentioning
confidence: 99%
“…A principal forma de transmissão do HIV é por meio da relação sexual desprotegida. Isso se deve, pelo baixo uso consciente do preservativo, que pode estar associado à possibilidade de diminuição do prazer e pode também ser potencializado quando acompanhado de uso de álcool ( Além disso, cada vez mais a população mais jovem está iniciando a vida sexual de forma precoce e muitas vezes sem o uso de preservativo, que pode ser parcialmente compensado pelo uso de anticoncepcional entre mulheres, aumentando sua vulnerabilidade sexual às Infecções Sexualmente Transmissíveis (IST), ao vislumbrar apenas a prevenção de gravidez e consequentemente contribuindo no aumento do sexo desprotegido (LANTOS H, et al, 2018).…”
Section: Discussionunclassified